Dried blood spot immunoassay for the detection of pre-eclampsia in developing countries - Jokinen, Risto (My University, 2022)
Ninety-nine percent of deaths caused by pre-eclampsia occur in developing countries. The disorder can easily be treated if detected early enough. Traditionally diagnosis is made using maternal characteristics and medical histories, and it can be improved using biomarkers, for example, placental growth factor. There are immunoassays for detecting placental growth factor from maternal serum, but these are not optimal for developing countries. This could be solved using dried blood spots as sample material. Dried blood spot samples are easy to collect, store and transport and would therefore be suitable for use in developing countries. Three different non-competitive sandwich immunoassay concepts with monoclonal antibodies for the detection of placental growth factor from dried blood spots we optimized. First, the capture antibody was coated to the microtiter wells and a tracer antibody labelled with europium chelate was used for the detection. Second, biotinylated the capture antibody and coupled it with streptavidin-coated magnetic particles to capture the analyte and separate it from interfering components from the sample. The third antibody-coated microtiter wells were used to capture the analyte, but the tracer was changed to the antibody-coated upconverting nanoparticle to see if we could get higher separation from the background than with the europium labelled tracer. Assays were tested and optimized with dried blood spots made from whole blood spiked with placental growth factor. Coated well assay could achieve signal-to-background ratios of 1,68 and 3,24 with 30 and 100 pg/ml of placental growth factor, respectively, making it usable in the second to third trimester of pregnancy. Using magnetic particles did not improve the assay and had a lower signal to backgrounds, 1,17 and 1,57. The best signal to the background was achieved with upconverting nanoparticle assay, 2,92 and 3,14, but deviation could be as high as 60 %. Coated well and up-converting nanoparticle assay shows promise for use in centralised testing in developing countries, but further testing and optimization are needed.
Keywords: pre-eclampsia, dried blood spot, immunoassay